MARKETING STRATEGY FOR FOREIGN BRAND: NAVIGATING PRICE WARS AND NEW COMPETITORS IN INDONESIA (CASE STUDY: CHEMICAL AND ALLOY DISTRIBUTION COMPANY) - Mohammad Arfi Hernandi; Harimukti Wandebori (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Indonesia’s galvanizing chemical industry has become increasingly competitive because of rapid industrial growth, local market expansion, and the entry of new domestic and regional suppliers. CHEMICALLOY, a distributor of specialty chemicals from Germany, has long positioned itself as a premium supplier of specialty chemicals and alloy for galvanizing companies in Indonesia. However, because of the shifting customer preferences into faster delivery, competitive pricing, and localized service, it becomes a new challenge for them in this business. To remain competitive, CHEMICALLOY must adapt and modify its marketing strategy by understanding both internal capabilities and external industry situation now. This study used a qualitative case study approach supported by semi-structured interviews with galvanizing company representatives who were involved in the business, technical side, and decision making, including internal management. Analytical tools such as SWOT analysis were used to determine internal and external factors of company. Then it continued using TOWS matrix which was applied after identifying key internal and external factors to formulate strategic options. The analysis shows that CHEMICALLOY’s primary strengths are high product quality, technical expertise, and long-term supplier relationships, while its main weaknesses involve limited local responsiveness and high lead times. Opportunities exist in growing infrastructure demand, whereas threats come from aggressive local competitors and exchange rate volatility. The study proposes three main strategic implications: enhancing customer responsiveness through maximizing local warehousing and CRM integration, strengthening consultative and value-based selling to highlight efficiency benefits and profit to customers, and developing localized marketing initiatives to improve brand proximity. Overall, the results focus in integrating global product excellence with localized service responsiveness is critical for sustaining CHEMICALLOY’s competitive advantage in Indonesia’s galvanizing market.